Perceptions of the value of traditional ecological knowledge to formal school curricula: opportunities and challenges from Malekula Island, Vanuatu - McCarter Joe; Gavin Michael C (BMC, 2011)
Abstract Background The integration of traditional ecological knowledge (TEK) into formal school curricula may be a key tool for the revitalisation of biocultural diversity, and has the potential to improve the delivery of educational objectives. This paper explores perceptions of the value of TEK to formal education curricula on Malekula Island, Vanuatu. We conducted 49 interviews with key stakeholders (local TEK experts, educators, and officials) regarding the use of the formal school system to transmit, maintain, and revitalise TEK. Interviews also gathered information on the areas where TEK might add value to school curricula and on the perceived barriers to maintaining and revitalising TEK via formal education programs. Results Participants reported that TEK had eroded on Malekula, and identified the formal school system as a principal driver. Most interviewees believed that if an appropriate format could be developed, TEK could be included in the formal education system. Such an approach has potential to maintain customary knowledge and practice in the focus communities. Participants identified several specific domains of TEK for inclusion in school curricula, including ethnomedical knowledge, agricultural knowledge and practice, and the reinforcement of respect for traditional authority and values. However, interviewees also noted a number of practical and epistemological barriers to teaching TEK in school. These included the cultural diversity of Malekula, tensions between public and private forms of knowledge, and multiple values of TEK within the community. Conclusions TEK has potential to add value to formal education systems in Vanuatu by contextualising the content and process of curricular delivery, and by facilitating character development and self-awareness in students. These benefits are congruent with UNESCO-mandated goals for curricular reform and provide a strong argument for the inclusion of TEK in formal school systems. Such approaches may also assist in the maintenance and revitalisation of at-risk systems of ethnobiological knowledge. However, we urge further research attention to the significant epistemological challenges inherent in including TEK in formal school, particularly as participants noted the potential for such approaches to have negative consequences.